5x-1=-5x+1

Simple and best practice solution for 5x-1=-5x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-1=-5x+1 equation:


Simplifying
5x + -1 = -5x + 1

Reorder the terms:
-1 + 5x = -5x + 1

Reorder the terms:
-1 + 5x = 1 + -5x

Solving
-1 + 5x = 1 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-1 + 5x + 5x = 1 + -5x + 5x

Combine like terms: 5x + 5x = 10x
-1 + 10x = 1 + -5x + 5x

Combine like terms: -5x + 5x = 0
-1 + 10x = 1 + 0
-1 + 10x = 1

Add '1' to each side of the equation.
-1 + 1 + 10x = 1 + 1

Combine like terms: -1 + 1 = 0
0 + 10x = 1 + 1
10x = 1 + 1

Combine like terms: 1 + 1 = 2
10x = 2

Divide each side by '10'.
x = 0.2

Simplifying
x = 0.2

See similar equations:

| 7/2*63=7/2*2/7 | | M-5=11 | | (-x+7)*3= | | (g-7)(g+9)= | | 4v=8e-g | | 10m+3=38 | | 0.9=-log | | 2*-1=0 | | -2x^2-22x+24= | | 4v=8e | | 2x+2=0.50x+11 | | 5a+12=36 | | 3n-5n=3 | | (7x-6)=90 | | 5/7x35 | | 5(2x+6)=-3(4x-1) | | 4(m-2)=14 | | (4x+3)+(-2x+4)=y | | 4.7p+8.7p+2.6p=93.96 | | 18x-36=12x-24 | | 2.2=-log(x) | | -15x+43=-10x+28 | | 47=2+9w | | 3(5y+5)=5y+45 | | 4a+8b=x | | 1/x=7/30 | | 16x+191=8x+127 | | -14x-153=-7x-90 | | -r/3=-100 | | -14+135=-7x+79 | | Y-z=x-y | | 17x+60=9x+36 |

Equations solver categories